A comparative meta‐analysis on the relationship of faecal calcium and phosphorus excretion in mammals. Issue 2 (26th November 2017) - Böswald, L. F.; Dobenecker, B.; Clauss, M.; Kienzle, E.
Summary: To investigate the relationship between faecal calcium (Ca) and phosphorus (P) excretion in different mammalian species, a meta‐analysis on digestibility data derived from the literature was conducted. Seventy‐three studies on carnivores, omnivores, large and small hindgut fermenters, ruminants and hippos (a total of 21 mammalian species, precondition for inclusion dietary Ca/P ratio 1.5/1 – 3.0/1) were analysed for Ca and P digestibility. Dietary Ca/P ratios were lower than faecal Ca/P ratios in carnivores, omnivores, ruminants and hippos. In hindgut fermenters, dietary Ca/P ratios were higher than faecal Ca/P ratios, indicating higher intestinal Ca absorption in these species. In all species investigated, there was a significant positive relationship between Ca intake and faecal Ca excretion and between P intake and faecal P excretion. In the biologically relevant range, these equations predicted lower faecal Ca losses in hindgut fermenters than ruminants, for faecal P vice versa. In all species, faecal Ca and P excretion correlated significantly. In carnivores, this highly linear correlation was exceptionally strong (R² = .92). Yet, the linearity of the correlation was questionable in omnivores and ruminants. Possibly, the strong linear correlation of faecal Ca and P excretion in carnivores is due to the formation of insoluble Ca/P complexes in their relatively short and simple gastrointestinal tract. Another hypothesis is that in carnivores, Ca homeostasis relies on modifying bone turnover to a higher degree than on changes in intestinal Ca absorption. For the formation of bone matrix, a constant ratio of Ca and P absorption is of advantage.